Pre-post feasibility trial of a telephone-delivered exercise intervention for patients during chemotherapy for recurrent ovarian cancer: the ECHO-R trial protocol - Andreas Obermair; Monika Janda; Sandra C Hayes; Elizabeth Eakin; Marcelo Nascimento; Dimitrios Vagenas; Jermaine Coward; Louisa G Gordon; Catherine Shannon; James Nicklin; Jeffrey Goh; Vanessa L Beesley; et al. (BMJ Open, 2024)
Introduction The benefits of exercise in reducing treatment-related morbidity and improving quality of life following a primary diagnosis of cancer have been well documented and have led to exercise being recommended by oncology societies for all people with a cancer diagnosis. However, these recommendations are derived from research typically involving cohorts with more common cancers and relatively good prognosis, such as breast and prostate. Evidence from these cancers may not apply to women with recurrent ovarian cancer. Therefore, the primary objective of this trial is to evaluate the feasibility and safety of a home-based, telephone-delivered exercise intervention for women undergoing chemotherapy for recurrent ovarian cancer.Methods and analysis The Exercise During Chemotherapy for Recurrent Ovarian Cancer (ECHO-R) trial is a single-arm, phase II, pre/postintervention trial of a 6-month, telephone-delivered exercise intervention (consistent with recommended exercise oncology prescription). The target sample size is 80 women who are currently undergoing (or are scheduled to receive) chemotherapy for recurrent ovarian cancer. Recruitment is through participating hospital sites in Queensland, Australia, or via self-referral. The exercise intervention comprises 12 telephone sessions over a 6-month period delivered by trial-trained exercise professionals and supplemented (where feasible) by five sessions face to face. Exercise prescription is individualised and works towards an overall goal of achieving a weekly target of 150 min of moderate-intensity, mixed-mode exercise. Assessments via self-administered survey and physical fitness and function tests occur at baseline and then at 6 and 9 months postbaseline. Data to inform feasibility and safety are recorded as case notes by the exercise professional during each session.Ethics and dissemination Ethics approval for the ECHO-R trial was granted by the Metro North Human Research Ethics Committee (HREC/2020/QRBW/67223) on 6 November 2020. Findings from the trial are planned to be disseminated via peer-reviewed publications and both national and international exercise and oncology conferences.Trial registration number ACTRN12621000042842.